2018
DOI: 10.3389/fendo.2018.00517
|View full text |Cite
|
Sign up to set email alerts
|

Progestin and Nuclear Progestin Receptor Are Essential for Upregulation of Metalloproteinase in Zebrafish Preovulatory Follicles

Abstract: Ovulation requires proteinases to promote the rupture of ovarian follicles. However, the identity of these proteinases remains unclear. In our previous studies using RNA-seq analysis of differential expressed genes, we found significant down-regulation of five metalloproteinases: adam8b (a disintegrin and metalloproteinase domain 8b), adamts8a (a disintegrin and metalloproteinase with thrombospondin motif 8a), adamts9, mmp2 (matrix metalloproteinase 2), and mmp9 in the nuclear progestin receptor knockout (pgr−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 47 publications
6
47
0
Order By: Relevance
“…The role of Pgr in ovulation is highly conserved across vertebrate species, as is evidenced by the inability of Pgr knockout female zebrafish, rats, and mice to ovulate (Kubota et al 2016, Lydon et al 1995, Zhu et al 2015. Further studies indicated that Pgr is an upstream regulator important for the increased expression of proteolytic enzymes and therefore promotes the rupture of follicles for releasing mature oocytes during ovulation (Liu et al, 2017(Liu et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The role of Pgr in ovulation is highly conserved across vertebrate species, as is evidenced by the inability of Pgr knockout female zebrafish, rats, and mice to ovulate (Kubota et al 2016, Lydon et al 1995, Zhu et al 2015. Further studies indicated that Pgr is an upstream regulator important for the increased expression of proteolytic enzymes and therefore promotes the rupture of follicles for releasing mature oocytes during ovulation (Liu et al, 2017(Liu et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…46 Our previous study identified adamts9, expressed in follicle cells, as a downstream target of Pgr, which is essential for ovulation in zebrafish. 47,48 However, it is worth noting that theca cells are also vital to the mammalian ovulatory process. 49 It has been reported that Adamts1 mRNA in the theca interna was upregulated just prior to ovulation in the horse.…”
Section: Discussionmentioning
confidence: 99%
“…Since PGR is expressed by granulosa cells and plays a critical role in ovulation, studies have focused on granulosa cells and revealed that PGR‐regulated genes unequivocally linked to the ovulatory success are the extracellular matrix proteases, for example, ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) family members 46 . Our previous study identified adamts9 , expressed in follicle cells, as a downstream target of Pgr, which is essential for ovulation in zebrafish 47,48 . However, it is worth noting that theca cells are also vital to the mammalian ovulatory process 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Various stages of AB wildtype embryos were collected at different times of development. Ovarian follicles were divided into different stages according to follicular size and morphological criteria [26] with a slight modi cation [21][22][23] . Stage I, III, IVb and V ovarian follicles were collected from 4-month old mature female AB wildtype sh between 7:00am and 8:30am (lights on photoperiod 8:30am-10:30pm).…”
Section: Collection Of Ovarian Follicles and Embryos And Extraction Omentioning
confidence: 99%
“…Our previous studies suggest Adamts9 is critical for normal development of ovaries and ovulation in the zebra sh [21][22][23][24] . In the present study, we examined expression of Adamts9 in the embryonic development and its roles in germ cell migration.…”
Section: Introductionmentioning
confidence: 97%